Usulan Konsep Design Ergoclass Menggunakan Evaluasi Cognitive Failure Questionnare dan DirecRT (Studi Kasus: Jurusan Matematika UIN SUSKA RIAU) - Nofirza Nofirza; Mela Defi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2021)
The classroom is one of the important factors in supporting lecturing activities. There are several facilities in the class which support the success of student learning processes namely chairs, tables, and blackboards as display aid in the lecturing. Mathematics UIN SUSKA Riau’s classroom does not currently consider cognitive ergonomics. This can be seen from complaints experienced by students while using facilities in the class. The purpose of this study is to improve the classroom considering cognitive ergonomics. This study used the CFQ method to determine the level of cognitive failure of students. Students are provideed with a test using the PEBL software to determine the reaction time speed in short-term memory and long-term memory. Based on this method, the student's cognitive failure rate is at moderate and high levels. As many as 65.5% of students are at moderate cognitive failure rates and 32.2% of students are at a high level of cognitive failure. The suggested design of the classroom is in the form of facilities design and an addition of a stage in front of the class, also a board with size based on the level of cognitive failure, complaints and anthropometry of students. The results of the study are expected to improve cognitive and student body posture, so the lecturing process can support the need of the students.Keyword: Antropomentric, classroom facilities, Cognitive Ergonomics